2011
DOI: 10.1088/0026-1394/49/1/005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different vibration exciter systems on high frequency primary calibration of single-ended accelerometers: II

Abstract: During the monitoring of the long term stability of two accelerometers intended for the use in the CIPM Key Comparison CCAUV.V-K2 significant deviations of the magnitude results of the single ended transducer were discovered. These deviations depend on whether the calibration was performed on an armature made of Beryllium or of ceramic. Further investigations exhibited that this effect must be attributed to some not yet readily understood dynamic process between the contact surfaces of accelerometer and armatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…As with all primary accelerometer calibrations, [38][39][40][41][42] there are many parasitic dynamic effects that can lead to systematic errors. For instance, we found that it was important to consider non-rigid body motion of the accelerometer package.…”
Section: A Harmonic Vibration Testingmentioning
confidence: 99%
“…As with all primary accelerometer calibrations, [38][39][40][41][42] there are many parasitic dynamic effects that can lead to systematic errors. For instance, we found that it was important to consider non-rigid body motion of the accelerometer package.…”
Section: A Harmonic Vibration Testingmentioning
confidence: 99%
“…The uncertainty of the specified confidence is as follows:U normalC = u A 2 + u B 2 . According to the previous analysis, the uncertainty of the system can be obtained by taking the horizontal stage as an example, as shown in Table 2. At the same time, it can be known whether the calibration accuracy of the vibration calibration system has been improved; the key factors are as follows: As far as possible, the standard vibration table can minimise the error of the excitation signal, and the single frequency sinusoidal excitation signal can be realised as far as possible, namely, the distortion degree of the system, the uneven surface of the table, and the transverse motion are minimised. The work environment of the laser interferometer is small, and it is properly installed and designed to reduce the measurement error caused by the light path. The effective vibration isolation measures for the system can also reduce the vibration interference of the system and reduce the random uncertainty error of the system. Using more precise and advanced electronic components and instruments to reduce the influence of the system error on the calibration accuracy of the system [8]. …”
Section: Research Contentmentioning
confidence: 99%
“…Bruns et al have considered in a second publication [6] the inclusion of additional spring and damping elements in the mathematical modeling for a primary calibration of an SE accelerometer, in order to consider finite contact stiffness between the accelerometer and the armature. It was concluded that there are strong evidences that the cause of the problem is a non-negligible relative motion between the SE transducer and the shaker armature at high frequencies.…”
Section: Dispersion Observed In Different Excitersmentioning
confidence: 99%
“…This has been reported by Dr. Thomas Bruns in 2009, during the IMEKO TC 22 technical meeting in Lisbon. Later on, two articles related to this problem were published in Metrologia [5] [6].…”
Section: Introductionmentioning
confidence: 99%